Performance of a Single Cylinder Diesel Engine Fueled by 40% Biodiesel Blend with Excess Air System - Firdausah, Risco Eka; Ilminnafik, Nasrul; Asrofi, Mochamad (Journal of Mechanical Engineering, Science, and Innovation, 2025)
In recent years, advances in science and technology have changed human lifestyles and increased global energy consumption. The global innovative search for alternative fuels from renewable sources such as biomass has become important, such as biodiesel. The use of biodiesel in diesel engines requires changes in air supply. Proper air supply is needed to obtain optimal engine performance. The purpose of this study was to determine the effect of using an excess air system on engine performance and exhaust emissions in diesel engines with a mixture of dexlite and biodiesel fuels. The research method used is experimental research and the parameters in this study include the use of an excess air system of 10 L / m, 20 L / m and a load of 300, 400, 500 Watt with biodiesel fuel (B40). The results of this study with the presence of an excess air system can increase combustion efficiency, thus increasing engine engine powerand torque with the most efficient engine power and torque, namely 4.87 KW at a load of 500 watts and 3.101 Nm at a load of 500 watts with excess air of 20 L/m. Fuel consumption also decreases with the presence of an excess air system at 10 L/m load 300 with a value of 0.16 kg/hour. The excess air system can also reduce CO and HC exhaust emissions with excess air of 20 L/m and a load of 300 watts, namely a CO value of 0.02%, an HC value of 18.2 ppm. So the use of excess air is effective in improving engine performance and emissions.